The effect of employing different raster orientations on the mechanical properties and microstructure of Fused Deposition Modeling parts - A. W. , Fatimatuzahraa; Baharuddin, Farahaina; Wan Yusoff, Wan Ahmad Yusmawiza (2011)
Rapid prototyping (RP) fulfills the current need in manufacturing industry to shorten the design cycle while improving its quality. Since there are various methods of RP process, this study focuses on the mechanical properties and microstructure of fused deposition modeling (FDM) RP specimens between two types of raster orientation which are cross (0°/90°) and crisscross (45°/-45°).The method of investigation in order to compare the result is done by doing several tests. The tests conducted throughout the research are; tensile, bending, impact and deflection test. The material used is Acrylonitrile Butadiene Styrene (ABS): a terpolymer of acrylonitrile, butadiene and styrene. The findings from this research are used to evaluate which parameters give the best result and performance besides improving the quality of a design for better product development.